The Manchurian Candidate (1962): An Interview with David Amram - Rosar, William H. (Journal of Film Music, 2009)
For a course in film music analysis, part of the University of Southern California’s Scoring for Motion Pictures and Television Program curriculum, I required my composer students to analyze a film score, preferably one of their own choosing. In addition to finding a copy of the score, if extant, students were also to research what the composers themselves thought about what they had written that might yield both insights about the music and its role in a film. If living, and wherever possible, I encouraged a student to interview the film composer whose score they were studying, and in some instances, I conducted the interview together with the student. One student, Peter Bloesch, was fascinated by the main theme of David Amram’s score for John Frankenheimer’s political intrigue-suspense thriller, the critically acclaimed The Manchurian Candidate (1962). Peter had transcribed the theme by ear as heard in the main title, since the whereabouts of the score itself was unknown at the time. He wanted to know Amram’s thoughts about the theme, its style, and how it related to the score in the film as a whole. We interviewed Amram by phone November 6, 1990, just 10 ten days before his 60th birthday. In addition to talking about Manchurian Candidate, the composer was very forthcoming with his own views on a variety of musical topics, including his own philosophy of music and aesthetics, especially as relates to composing film music. The transcript that follows has been edited and revised for publication here by Amram and myself.